Alpha-linolenic acid-mediated epigenetic reprogramming of cervical cancer cell lines - Amrita Ulhe; Prerna Raina; Amol Chaudhary; Ruchika Kaul-Ghanekar (Epigenetics)
Cervical cancer, the fourth most common cancer globally and the second most prevalent cancer among women in India, is primarily caused by Human Papilloma Virus (HPV). The association of diet with cancer etiology and prevention has been well established and nutrition has been shown to regulate cancer through modulation of epigenetic markers. Dietary fatty acids, especially omega-3, reduce the risk of cancer by preventing or reversing the progression through a variety of cellular targets, including epigenetic regulation. In this work, we have evaluated the potential of ALA (α linolenic acid), an ω-3 fatty acid, to regulate cervical cancer through epigenetic mechanisms. The effect of ALA was evaluated on the regulation of histone deacetylases1, DNA methyltransferases 1, and 3b, and global DNA methylation by ELISA. RT-PCR was utilized to assess the expression of tumor regulatory genes (hTERT, DAPK, RARβ, and CDH1) and their promoter methylation in HeLa (HPV18-positive), SiHa (HPV16-positive) and C33a (HPV-negative) cervical cancer cell lines. ALA increased DNA demethylase, HMTs, and HATs while decreasing global DNA methylation, DNMT, HDMs, and HDACs mRNA expression/activity in all cervical cancer cell lines. ALA downregulated hTERT oncogene while upregulating the mRNA expression of TSGs (Tumor Suppressor Genes) CDH1, RARβ, and DAPK in all the cell lines. ALA reduced methylation in the 5’ CpG island of CDH1, RARβ, and DAPK1 promoters and reduced global DNA methylation in cervical cancer cell lines. These results suggest that ALA regulates the growth of cervical cancer cells by targeting epigenetic markers, shedding light on its potential therapeutic role in cervical cancer management.